Recent Biomaterial Developments for Bone Tissue Engineering and Potential Clinical Application: Narrative Review of the Literature - Abu Owida , Hamza; Al-Ayyad , Muhammad; Turab, Nidal M.; Al-Nabulsi , Jamal I. (International Journal of Online and Biomedical Engineering (iJOE), 2023)
Over the course of time, there has been a progression in the materials utilized for implants, transitioning from inert substances to those that replicate the structural characteristics of bone. Consequently, there has been a development of bioabsorbable, biocompatible, and bioactive materials. This article presents a comprehensive survey of diverse biomaterials with the potential to serve as scaffolds for bone tissue engineering. The objective of this study is to present an in-depth review of the predominant biomaterials utilized in the fabrication of scaffolds. This review encompasses the origins, classifications, characteristics, and methodologies involved in the development of these biomaterials. The review also highlights the incorporation of additives in biomaterial scaffolds. This study ultimately underscores the potential advantages and challenges associated with the utilization of biomaterials in scaffolds for bone tissue engineering. Additionally, it critically examines the integration of state-of-the-art technology with biomaterials.